THE ROLE OF CROWDFUNDING PLATFORMS IN DEVELOPING WOMEN'S HUMAN CAPITAL (Scientific electronic journal "Labor Economics and Human Capital", 2024)
The article examines and reflects the role and significance of crowdfunding platforms in the development of women's human capital along with other financial resources, the role and significance of crowdfunding platforms in the development of women's human capital, assesses the rationality (reasonableness) of using crowdfunding, provides an algorithm for presenting a project on a crowdfunding platform.
Keywords: women's human capital, crowdfunding platform, business idea, investment methods, sources of funding.